Portfolio management in new product development lessons from the leaders I - Cooper, Robert G. (Research management (Now: research technology management))
Robert G. Cooper, Scott J. Edgett and Elko J. Kleinschmidt report how leading firms attempt to maximize the value of their R&D portfolios and achieve the right product balance and mix.